Numerical simulation of premixed Hydrogen/air combustion pressure in a spherical vessel - Guo Han-yu; Tao Gang; Zhang Li-jing (MATEC Web of Conferences, 2016)
In order to study the development process of hydrogen combustion in a closed vessel, an on-line chemical equilibrium calculator and a numerical simulation method would be used to analysis the combustion pressure and flame front of mixed gas, which based on 20L H2/air explosion experiments in spherical vessel (Crowl and Jo,2009). The results showed that, the turbulent model could reflect the process of combustion, and the error of combustion pressure by simulation is smaller than the Chemical Equilibrium Calculation. The heat loss and incomplete combustion are the main reason to cause the error.